2019
DOI: 10.1007/s40556-018-0190-2
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Analysis of Spontaneous Miscarriages Using Long-Term Culturing of Chorionic Villi

Abstract: Spontaneous miscarriages are strongly associated with fetal chromosomal abnormalities. We sought to validate the occurrence of chromosomal abnormalities in Japanese patients with early spontaneous miscarriages using a conventional long-term culture method. One hundred and thirty-two patients were studied after excluding 7 cases with culture failure. Chromosomal analysis of 132 cases was performed using a long-term culture method of the villous placental tissue. Patients' age, number of previous spontaneous abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…In our study we have found higher abnormality rate (29%) in advanced maternal age group as compare to younger population studied (17%). The present findings consistent with the studies that reported the increased incidence of chromosomal abnormality with increasing maternal age [14][15][16]. Various studies have concluded that the women's with advanced maternal age have a higher incidence of unfavourable reproductive outcomes such as complications during pregnancy, spontaneous pregnancy loss, infertility or congenital anomalies in foetus as compared to the younger women which is consistent with the present study [17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 93%
“…In our study we have found higher abnormality rate (29%) in advanced maternal age group as compare to younger population studied (17%). The present findings consistent with the studies that reported the increased incidence of chromosomal abnormality with increasing maternal age [14][15][16]. Various studies have concluded that the women's with advanced maternal age have a higher incidence of unfavourable reproductive outcomes such as complications during pregnancy, spontaneous pregnancy loss, infertility or congenital anomalies in foetus as compared to the younger women which is consistent with the present study [17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 93%
“…Only few stratified analyses on the correlation between the incidence of single autosomal trisomies and maternal age are available, and a direct comparison is difficult due to differently formatted data. However, there are some previous studies where a higher rate of single autosomal trisomy was observed in older women [ 16 , 19 , 46 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found an increased abnormality rate (58.7%) compared with most previous studies [ 14 , 19 , 38 , 41 , 42 , 43 , 44 , 45 ]. However, there are reported data in which the abnormality rate was higher [ 2 , 16 , 19 , 31 , 46 ]. Our findings compared to the relative frequencies of different types of chromosome abnormalities along with the ones reported in previous studies are shown in Table 5 .…”
Section: Discussionmentioning
confidence: 99%